Desarrollo de una aplicación de guía turística interactiva para dispositivos móviles que permita al turista conocer y ver etiquetada la información relevante de los lugares más importantes de la ciudad de Loja, basada en la realidad aumentada. - Chuico Muñoz, Alex Lenin, Miguel Antonio Paredes Cañar (2015)
Thesis project is a proposal for the promotion process in the field of tourism to nationally and international level through mobile technology and augmented reality that is capable of mixing places about touristic interest with relevant information. The application of tourist guide has a friendly interface able to provide tourist information to tourists, in the same way the monitoring and recording of information of the tourist sites and also provides a map with sites in order to guide users drawing a route to a desired site of interest. The aim of the following project is to develop an application for mobile devices with technology based on augmented reality for the Android operating system. The application, using the GPS service, accelerometer and compass from the mobile detects the user's location, it gets the sights of interest nearby where you can by simply focusing the camera phone to the desired location and the application will show information about each of these in the databases available on a server. The format of the screens is developed in XML and will be used easily by the user without much computer knowledge. The purpose of this project is to develop an application that serves as a platform for future developments in the field of tourism and that students engage in a full draft some length. The project includes five chapters that were considered parameters that they have helped the knowledge for the proper development of the application. Chapter I. Here it points this methodological aspects applied to the development of the application, which they have the Iconix methodology with a description of its phases, an analysis of UML modeling language and designs that includes modeling. Chapter II. It specifics programming tools to use such as: Eclipse, Java, MySQL, PHP, Apache, phpMyAdmin, Mercurial, Bitbucket Chapter III. It details aspects in order to have a general knowledge of the operation, features and technology that have mobile devices. Chapter IV. In this chapter it express the benefits of augmented reality technology and applied fields to merge the touristic sites with the relevant information. Chapter V. Here it mentions related knowledge with android operating system using mobile devices for its functionality. Chapter VI. In this final chapter we specify the relevant information from touristic places the most important of the city of Loja. The technique used for collecting data was a survey whose questions are fundamental for the functional requirements provided by the surveyed users. The interpretation of the results is supported in the respective statistical tables that show the importance of the issue and use of an application for the tourism field. In developing this application they have been reused existing libraries as google-play-services.jar to use google map and wikitudesdk.jar to integrate augmented reality technology to the project, it has also conducted a study of alternatives for be included in an Android application The foundation base of this work shows that it is necessary that the process of promoting tourism is conducted with the use of a deployed application with augmented reality technology, which it integrates with the mobile services GPS, camera and Internet access, in order to acquire a process in efficient way and integrity.